Practical Perspectives of 1, 4‐Dioxane Investigation and Remediation. Issue 1 (5th December 2016) - Chiang, Sheau‐Yun (Dora); Anderson, Richard (Hunter); Wilken, Michael; Walecka‐Hutchison, Claudia
Abstract : 1, 4‐Dioxane (dioxane) is a contaminant of emerging concern that is classified by the U.S. Environmental Protection Agency as a likely human carcinogen. Dioxane has been used as a minor or major ingredient in many applications, and is also generated as an unwanted by‐product of industrial processes associated with the manufacturing of polyethylene, nonionic surfactants, and many consumer products (cosmetics, laundry detergents, shampoos, etc.). Dioxane is also a known stabilizer of chlorinated solvents, particularly 1, 1, 1‐trichloroethane, and has been commonly found comingled with chlorinated solvent plumes. Dioxane plumes at chlorinated solvent sites can complicate site closure strategies, which to date have not typically focused on dioxane. Aggressive treatment technologies have greatly advanced and are clearly capable of achieving lower parts per billion cleanup criteria using ex situ advanced oxidation processes and sorption media. In situ chemical oxidation has also been demonstrated to effectively remediate dioxane and chlorinated solvents. Other in situ remedies, such as enhanced bioremediation, phytoremediation, and monitored natural attenuation, have been studied; however, their ability to achieve cleanup levels is still somewhat questionable and is limited by co‐occurring contaminants. This article summarizes and provides practical perspectives on dioxane analysis, plume stability relative to other contaminants, and the development of investigation tools and treatment technologies.